Key points and time intervals for early diagnosis in symptomatic oral cancer: a systematic review. Issue 1 (January 2017) - Varela-Centelles, P.; López-Cedrún, J.L.; Fernández-Sanromán, J.; Seoane-Romero, J.M.; Santos de Melo, N.; Álvarez-Nóvoa, P.; Gómez, I.; Seoane, J.
Abstract: The aim of this study was to identify key points and time intervals in the patient pathway to the diagnosis of oral cancer, from the detection of a bodily change to the start of treatment. A systematic search of three databases was performed by two researchers independently. Articles reporting original data on patients with symptomatic primary oral or oropharyngeal squamous cell carcinoma that was pathologically confirmed were included. These articles had to include an outcome variable of 'diagnostic delay', 'time interval', or 'waiting time to diagnosis', or report time intervals from first symptom to treatment. Furthermore, the outcome variable had to have a clearly defined start point and end point, with the time measurement presented as a continuous or categorical variable. A total of 1175 reports were identified; 28 articles on oral cancer studies and 13 on oral and oropharyngeal cancer studies were finally included. These papers showed poor quality in terms of questionnaire validation, acknowledgement of biases influencing time-point measurements, and strategies for verification of patient self-reported data. They also showed great heterogeneity. The review findings allowed the definition of key points and time intervals within the Aarhus framework that may better suit the features of the diagnostic process of this neoplasm, particularly when assessing the impact of waiting time to diagnosis.